Mapping Inner Space. - Ochoa, Emily (American Scholar)
The article discusses the creation of a brain map that depicts which parts of the human brain process different types of objects by neuroscientists at the University of California (UC) at Berkeley. The researchers did this by conducting magnetic resonance imaging (MRI) scans of test-subjects' brains as they viewed movies. It is argued that such a map could eventually lead to the creation of computers that identify objects in the same ways as humans.